2014
DOI: 10.2337/dc13-2900
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss, Glycemic Control, and Cardiovascular Disease Risk Factors in Response to Differential Diet Composition in a Weight Loss Program in Type 2 Diabetes: A Randomized Controlled Trial

Abstract: OBJECTIVETo test whether a weight loss program promotes greater weight loss, glycemic control, and improved cardiovascular disease risk factors compared with control conditions and whether there is a differential response to higher versus lower carbohydrate intake.RESEARCH DESIGN AND METHODSThis randomized controlled trial at two university medical centers enrolled 227 overweight or obese adults with type 2 diabetes and assigned them to parallel in-person diet and exercise counseling, with prepackaged foods in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 31 publications
4
127
0
10
Order By: Relevance
“…These results are consistent with some previous studies (6,(8)(9)(10). However, other studies have shown greater HbA1c reductions with a very-low-carbohydrate diet (7,27,28) that could be explained by differences in energy intakes and weight loss between the very-low-carbohydrate and HC diets examined. The 1% HbA1c reduction achieved in the current study is comparable with the reductions observed in the Look AHEAD (Action for Health in Diabetes) study (from 7.3% to 6.6%) after an intensive lifestyle intervention in T2D (36).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with some previous studies (6,(8)(9)(10). However, other studies have shown greater HbA1c reductions with a very-low-carbohydrate diet (7,27,28) that could be explained by differences in energy intakes and weight loss between the very-low-carbohydrate and HC diets examined. The 1% HbA1c reduction achieved in the current study is comparable with the reductions observed in the Look AHEAD (Action for Health in Diabetes) study (from 7.3% to 6.6%) after an intensive lifestyle intervention in T2D (36).…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies that compared ad libitum very-low-carbohydrate diets with calorie-restricted HC diets in T2D reported mixed results with some studies reporting greater weight loss after a very-low-carbohydrate diet (11,28), and others reporting no differential effect (6)(7)(8)10). In the current study, diets were isocalorically prescribed and achieved comparable weight loss, which suggested that the caloric deficit, independent of the macronutrient composition, is the primary determinant of weight loss.…”
Section: Discussionmentioning
confidence: 96%
“…Dietary intake restriction interventions in T2DM patients lead to improvements in glycaemic control, insulin sensitivity, the lipid profile, endothelial dysfunction, LV diastolic function and body composition [72][73][74][75][76]. Because some of these parameters are believed to be related to development of CI, it should thus be examined whether such an intervention will also lead to improved HR responses to exercise in T2DM patients with CI.…”
Section: Dietary Intake Restriction Intervention In T2dm Patients Witmentioning
confidence: 96%
“…En otros 4 se encontró mayor reducción en el grupo DBCH (14,17,19,21), y en el resto no hubo diferencias entre grupos. En ningún caso se encontraron diferencias estadísticamente significativas con respecto a los niveles de colesterol total.…”
Section: Valores Lipídicosunclassified